Enhancing the electroactive phases in freestanding flexible films of MoS2/PVDF. Issue 2 (5th November 2020) - Thakur, Abhishek; Mandeep, Jangra; Dam, Siddhartha; Shekar, N. V. Chandra; Amarendra, G.; Hussain, Shamima; Rajesh, P. V.; Saha, Abhijit
Abstract: Freestanding, flexible, composite thin films of MoS2 /PVDF have been synthesized using sol–gel method. Concentration of the fillers was optimized to tune the formation of electroactive phases (EA). The maximum amount of EA phases was obtained for 1 wt% of filler concentration. The as‐prepared samples were characterized to understand the effect of fillers on their microstructural, vibrational, and morphological properties. The fractions, of both β and γ phases, were calculated from infrared spectra. An enhancement of the EA phase from 28% to 83% was observed with the addition of 1 wt% of nanoflake fillers. The fillers were found to reduce the crystallinity of the host polymer matrix. Additionally, the morphology shows a change from spherulitic to fibrous nature with the appearance of nanoflakes on the surface for higher filler concentrations. The nanoflakes induce interfacial polarization. The intercalation of nanoflakes into the host matrix, leads to the observed trends. Abstract : MoS2 nanoflakes were dispersed in polyvinylidene fluoride (PVDF) solution. The films show enhanced electroactive components due to interfacial polarization. MoS2 nanoflakes polarize the polymer chain locally and reorient them.